The need to consider auxiliary assumptions in preregistration practices - St Quinton, Tom; Trafimow, David (Frontiers in Psychology, 2025)
The importance of preregistration has gained recent traction in psychology. To reduce questionable research practices and improve the credibility of research findings, researchers preregister important details before commencing with data collection. However, current preregistration practices miss an important issue when it comes to evaluating predictions. That is because predictions depend not only on theoretical terms but also auxiliary assumptions. Auxiliary assumptions traverse the distance from nonobservational theoretical terms to observational terms at the level of the empirical hypotheses. Because the credibility of study findings depends on the appraisal of auxiliary assumptions, these assumptions should, at least, be considered in preregistration practices. In this paper we outline the need to consider auxiliary assumptions during preregistration, the benefits of doing so, and how current practices can be amended to accommodate them. If the need for researchers to preregister continues to increase and the belief is that doing so will increase the credibility of psychological research, we believe auxiliary assumptions should become part of these practices.